Simultaneous selenium and sulfur speciation analysis in cultivated Pleurotus pulmonarius mushroom. (1st May 2019) - Milovanovic, Ivan; Lajin, Bassam; Braeuer, Simone; Steiner, Oliver; Lisa, Fasshold; Goessler, Walter
Highlights: Selenium speciation analysis in mycelium and fruiting body of P. pulmonarius . Simultaneous investigation of selenium and sulfur species in cultivated mushroom. Se-Met and Met are the dominant low molecular weight Se and S species in mushroom. Se-Met and Met are protein bound in the mycelium but free in the fruiting body. Abstract: Selenium (Se) and sulfur (S) speciation analysis in edible and medicinal Se enriched P. pulmonarius extracts was performed. Mycelium, colonized substrate, and fruiting bodies at different harvesting times were analyzed using ion-pairing reversed-phase chromatography coupled to an ICPMS/MS detector. Extraction efficiencies in enzymatically digested and aqueous extracts were between 45.3 and 109% for Se, depending on the sample type. Selenomethionine (Se-Met) was found to be the major Se-compound, together with a number of unknown Se-species. Cystine (Cys2 ), methionine (Met), and sulfate were also detected and quantified in all samples. Most of the Se-Met (84.0%) and Met (75.8%) were found to be in free form in the fruiting body, in contrast with the mycelium where 53.4% of Se-Met and 80.5% of Met is incorporated into proteins.